You like it darker : stories - King, Stephen, 1947- (New York : Scribner, 2024)
"You like it darker? Fine, so do I," writes Stephen King in the afterword to this magnificent new collection of twelve stories that delve into the darker part of life--both metaphorical and literal. King has, for half a century, been a master of the form, and these stories, about fate, mortality, luck, and the folds in reality where anything can happen, are as rich and riveting as his novels, both weighty in theme and a huge pleasure to read. King writes to feel "the exhilaration of leaving ordinary day-to-day life behind," and in You Like It Darker, readers will feel that exhilaration too, again and again. "Two Talented Bastids" explores the long-hidden secret of how the eponymous gentlemen got their skills. In "Danny Coughlin's Bad Dream," a brief and unprecedented psychic flash upends dozens of lives, Danny's most catastrophically. In "Rattlesnakes," a sequel to Cujo, a grieving widower travels to Florida for respite and instead receives an unexpected inheritance--with major strings attached. In "The Dreamers," a taciturn Vietnam vet answers a job ad and learns that there are some corners of the universe best left unexplored. "The Answer Man" asks if prescience is good luck or bad and reminds us that a life marked by unbearable tragedy can still be meaningful. King's ability to surprise, amaze, and bring us both terror and solace remains unsurpassed. Each of these stories holds its own thrills, joys, and mysteries; each feels iconic. You like it darker? You got it. --
Two talented bastids -- The fifth step -- Willie the weirdo -- Danny Coughlin's bad dream -- Finn -- On Slide Inn Road -- Red screen -- The turbulence expert -- Laurie -- Rattlesnakes -- The dreamers -- The answer man
Keywords: Fate and fatalism -- Fiction; Mortality -- Fiction; Fortune -- Fiction; Widowers -- Fiction; Inheritance and succession -- Fiction; Horror fiction; Thrillers (Fiction); Short stories